Effect of RNA Interference Inhibiting the Expression of the FUBP1 Gene on Biological Function of Gastric Cancer Cell Line SGC7901 - Zhang, Fucheng; Zhang, Yingge; Wang, Yaojun (Turkish Journal of Gastroenterology, 2021)
Background: The research aimed to observe the effect of gene silencing on the proliferation, migration, cell cycle, apoptosis, and otherbiological functions of human gastric cancer cells with RNA interference inhibiting the expression of the far upstream element-bindingprotein 1 (FUBP1) in the gastric cancer cell line SGC7901.Methods: The shRNA lentivirus vector of the target gene FUBP1 was constructed to transfect the gastric cancer cell line SGC7901. TheqRT-PCR and western blot assays were used to detect the expression levels of FUBP1 mRNA and protein in the gastric cancer cells. TheCCK-8 assay was used to detect the proliferation of gastric cancer cells. The cell scratch assay and the transwell assays were used todetect the migration of gastric cancer cells. Flow cytometry was used to detect cell cycle distribution and apoptosis.Results: The shRNA lentiviral vector of FUBP1 was successfully transfected into the gastric cancer cell line SGC7901, and could effectively reduce the expression of mRNA and protein of FUBP1. The silencing of FUBP1 could inhibit the gastric cancer cell proliferation andaffect the distribution of the cell cycle, resulting in S-phase arrest and cell growth inhibition. However, FUBP1 silencing has no significanteffect on cell apoptosis and migration.Conclusions: The expression of FUBP1 can be inhibited specifically and effectively by RNA interference technology, which can significantly affect the biological function of the gastric cancer cell line SGC7901.